2006
DOI: 10.1590/s1984-63982006000100004
|View full text |Cite
|
Sign up to set email alerts
|

Técnicas de utilização de dicionário como material didático na aula de LE para fins específicos

Abstract: Este artigo apresenta uma metodologia de trabalho relacionado ao uso do dicionário como material didático na aula de língua estrangeira com fins específicos, em atividades como desenvolvimento de vocabulário, gramática, pronúncia, uso de língua, cultura, leitura e interpretação de texto. Com certas técnicas, os professores podem aproveitar esse material em suas aulas e orientar seus alunos sobre qual dicionário adquirir e como empregá-lo de maneira eficiente. Oferecemos algumas sugestões de atividades para ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The use of these tools in specific language areas has been asserted by other authors. Welker (2006a), for example, cited Höfling et al (2004) to show that the authors had suggested activities in the domain of pronunciation and grammar (p. 233). Rodrigues Liska (2015) suggested that learners use one of six dictionaries which are available online to do activities that deal with aspects of lexical items.…”
Section: Studies On Lexicography: Dictionaries Of the Portuguese Lang...mentioning
confidence: 99%
“…The use of these tools in specific language areas has been asserted by other authors. Welker (2006a), for example, cited Höfling et al (2004) to show that the authors had suggested activities in the domain of pronunciation and grammar (p. 233). Rodrigues Liska (2015) suggested that learners use one of six dictionaries which are available online to do activities that deal with aspects of lexical items.…”
Section: Studies On Lexicography: Dictionaries Of the Portuguese Lang...mentioning
confidence: 99%